Towards Feshbach Resonances in the S-WAVE Channel - Del Franco, Paul (University of Waterloo, 2024)
Ultracold molecules offer unique opportunities for studying quantum phenomena. This thesis presents work undertaken to repair and optimize an older experimental setup which last studied Feshbach resonances in the p-wave channel for ultracold Sodium-Lithium (NaLi) molecules. The primary focus of this work was on the process of repairing and reconfiguring the molecule machine back to a working state. This involved the repair of the optical systems which provide the laser light at the required frequencies. The characterization of the dual species atomic beam, leading to the replacement of the Sodium (Na) and Lithium (Li) sources. The re-optimization of the Zeeman slower current and light alignment. The alignment, configuration and optimization of the magneto optical trap, along with configuration of the transfer processes to the magnetic trap. Significant effort was dedicated to evaporative cooling, where we reached near quantum degeneracy temperatures for both species. With both ultracold gases, we optimized the transfer into an optical dipole trap where we could sweep a magnetic field to produce Feshbach molecules. Progress was made towards Stimulated Raman Adiabatic Passage (STIRAP) for efficient transfer into the triplet ground-state. Although the final step in the STIRAP process was not completed, the successful detection of Feshbach molecules was achieved. This work provides a solid foundation for future experiments, including the completion of the triplet ground-state molecule formation and enhanced stability which will allow for the exploration of s-wave Feshbach resonances in NaLi + NaLi collision complexes. This thesis contributes to the understanding of ultracold molecular interactions and offers insight into the problems encountered in the process of restoring and optimizing a complex experimental apparatus.
Keywords: NATURAL SCIENCES::Physics::Atomic and molecular physics::Atomic physics; Ultracold molecules; Feshbach resonances; p-wave channel; Sodium-Lithium (NaLi) molecules; Sodium; Lithium; Zeeman slower; magneto optical trap; Stimulated Raman Adiabatic Passage (STIRAP); triplet ground-state; s-wave \; optical dipole trap